A HOLISTIC APPROACH TO UNDERSTANDING HIV ADHERENCE PSYCHOSOCIAL DETERMINANTS AND QUALITY OF LIFE - Maria, Ima; Kusdiyah, Erny; Syauqy, Ahmad; Miftahurrahma, Miftahurrahma; Wulandari, Putri Sari; Darmawan, Armaidi; Aurora, Wahyu Indah Dewi (LPPM Universitas Jambi, 2026)
HIV remains a pressing public health issue in Indonesia, with Jambi City showing a steady increase in cases, especially among high-risk groups. This study aims to estimate the prevalence of HIV in Jambi City and examine various factors related to HIV infection, including socio-economic conditions, individual behaviors, and family history. It also explores public knowledge about HIV prevention, along with treatment adherence and quality of life among people living with HIV/AIDS (PLWHA). A cross-sectional study was conducted between August and September 2024 at four community health centers, involving 101 HIV-positive respondents who were undergoing antiretroviral therapy (ART). Data were collected through face-to-face interviews using validated questionnaires. The estimated HIV prevalence in Jambi City was 0.19%, based on average rates from the selected health centers. Among participants, 35.6% had low ART adherence, while 29.7% had high adherence. Better HIV prevention knowledge and fewer side effects were significantly associated with improved adherence. Additionally, having strong social support and being part of a peer-sharing community were linked to higher physical health-related quality of life. These findings highlight the need for more comprehensive HIV programs that not only focus on treatment but also strengthen education, manage treatment side effects, and build supportive community environments. This study offers a locally grounded perspective by combining prevalence estimates with psychosocial factors, providing useful input for targeted and sustainable intervention strategies in Jambi. The results may serve as a reference for health policymakers to design more integrated and context-appropriate HIV responses at the community level.